2021
DOI: 10.3389/fcell.2021.747722
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diluent pH on Enrichment and Performance of Dairy Goat X/Y Sperm

Abstract: In this paper, on the basis of the differences in the hydrogen ion concentration (pH) of the diluent dairy goat semen on X/Y sperm motility, an X/Y sperm enrichment study was conducted to establish a simple and effective method for gender control in dairy goats. Dairy goat semen was diluted using different pH dilutions and was incubated. Then, the X/Y sperm ratio in the isolated upper sperm was determined using the double TaqMan qPCR method. The internal pH change pattern of sperm cells at different pH dilutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 69 publications
(84 reference statements)
1
6
0
Order By: Relevance
“…The proportion of intact and uncapacitated sperm in the upper and lower layers was not significantly different from the control group after incubation at pH 7.4 for 40 min. This is consistent with the results of previous studies that used enriched sperm for in vitro fertilization and found no difference in the fertilization rate between the test and the control groups [ 11 ]. A schematic diagram of the mechanism of the effect of the pH of the dilution solution on sperm motility is shown in Figure 10 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The proportion of intact and uncapacitated sperm in the upper and lower layers was not significantly different from the control group after incubation at pH 7.4 for 40 min. This is consistent with the results of previous studies that used enriched sperm for in vitro fertilization and found no difference in the fertilization rate between the test and the control groups [ 11 ]. A schematic diagram of the mechanism of the effect of the pH of the dilution solution on sperm motility is shown in Figure 10 .…”
Section: Discussionsupporting
confidence: 93%
“…We established in a previous study [ 11 ] ( Figure 1 A) that the pHi of the sperm in the upper and lower layers of a test tube increased to 6.9 (initial 5.01) over 10 min and then remained unchanged when incubated in a diluent of pH 7.4 ( Figure 1 B,C). The total motility and forward motility of spermatozoa in the upper layer of the tube were found to be significantly higher than that of spermatozoa in the lower layer ( Figure 1 D,E).…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations